Characterization of Pseudomonas spp. Associated with Spoilage of Gilt-Head Sea Bream Stored under Various Conditions - Tryfinopoulou, P. (American Society for Microbiology, 2002)
The population dynamics of pseudomonads in gilt-head sea bream Mediterranean fish (Sparus aurata) stored under different conditions were studied. Phenotypic analysis and sodium dodecyl sulfate-polyacrylamide gel electrophoresis of whole-cell proteins were performed to identify a total of 106 Pseudomonas strains isolated from S. aurata stored under different temperatures (at 0, 10, and 20°C) and packaging conditions (air and a modified atmosphere of 40% CO(2)-30% N(2)-30% O(2)). Pseudomonas lundensis was the predominant species, followed by Pseudomonas fluorescens, while Pseudomonas fragi and Pseudomonas putida were detected less frequently. Fluorescent Pseudomonas strains dominated under air conditions, while proteolytic and less lipolytic strains dominated under modified-atmosphere packaging. Different storage conditions appear to govern the selection of pseudomonads in gilt-head sea bream fish.